Colors of the blind. (China : Centre of International Cultural Exchange, China for.)
A blind girl named Ding Lihua is full of vigor and cherishes the beautiful visions for life and love. She had the opportunity to be trained professionally as an athlete. Sports built her character and it made her understand that life is more than falling in love.
Keywords: Cultural Center of China